Genomic Analysis of a mcr-9.1-Harbouring IncHI2-ST1 Plasmid from Enterobacter ludwigii Isolated in Fish Farming - Vera Manageiro; Vanessa Salgueiro; Tânia Rosado; Narcisa M. Bandarra; Eugénia Ferreira; Terry Smith; Elsa Dias; Manuela Caniça (MDPI AG, 2022)
This study analyzed the resistome, virulome and mobilome of an MCR-9-producing Enterobacter sp. identified in a muscle sample of seabream (Sparus aurata), collected in a land tank from multitrophic fish farming production. Average Nucleotide Identity analysis identified INSAq77 at the species level as an Enterobacter ludwigii INSAq77 strain that was resistant to chloramphenicol, florfenicol and fosfomycin and was susceptible to all other antibiotics tested. In silico antimicrobial resistance analyses revealed genes conferring in silico resistance to β-lactams (blaACT-88), chloramphenicol (catA4-type), fosfomycin (fosA2-type) and colistin (mcr-9.1), as well as several efflux pumps (e.g., oqxAB-type and mar operon). Further bioinformatics analysis revealed five plasmid replicon types, including the IncHI2/HI2A, which are linked to the worldwide dissemination of the mcr-9 gene in different antibiotic resistance reservoirs. The conserved nickel/copper operon rcnR-rcnA-pcoE-ISSgsp1-pcoS-IS903-mcr-9-wbuC was present, which may play a key role in copper tolerance under anaerobic growth and nickel homeostasis. These results highlight that antibiotic resistance in aquaculture are spreading through food, the environment and humans, which places this research in a One Health context. In fact, colistin is used as a last resort for the treatment of serious infections in clinical settings, thus mcr genes may represent a serious threat to human health.